Identification, Characterization, and Evaluation of Nematophagous Fungal Species of Arthrobotrys and Tolypocladium for the Management of Meloidogyne incognita - Kassam, Rami; Yadav, Jyoti; Chawla, Gautam; Kundu, Aditi; Hada, Alkesh; Jaiswal, Nisha; Bollinedi, Haritha; Kamil, Deeba; Devi, Prameela; Rao, Uma (Frontiers in Microbiology, 2021)
Root-knot nematodes (RKNs) belonging to the genus Meloidogyne are agriculturally important pests, and biocontrol strategies offer safer alternatives for their management. In the present study, two fungal species from Indian soils were identified as Arthrobotrys thaumasia and Tolypocladium cylindrosporum based on morphological characteristics and further confirmed using molecular markers. In vitro evaluation of A. thaumasia against M. incognita and Caenorhabditis elegans showed 82% and 73% parasitism, respectively, while T. cylindrosporum gave 65.2% and 57.7% parasitism. Similarly, culture filtrates of A. thaumasia caused 57.7% and 53.7% mortality of M. incognita and C. elegans, respectively while, T. cylindrosporum caused a higher mortality of 87.3% and 64%. Besides, greenhouse evaluation of both fungi against M. incognita infecting tomato significantly reduced nematode disease burden reflecting parasitic success measured as total number of galls, egg masses, eggs per egg mass, and derived nematode multiplication factor (MF). Application of A. thaumasia and T. cylindrosporum reduced nematode MF by 80% and 95%, respectively compared to control. General metabolite profiling of tested fungi using Gas-Chromatography–Mass Spectrometry (GC–MS) and Ultra Performance Liquid Chromatography-Quadrupole-Time of Flight Mass Spectrometry (UPLC-QToF-MS) reported for the first time here showed presence of various volatile and non-volatile compounds with nematicidal activity viz., trimethyl-heptadiene, methyl-hexadecanol, dodecadienal, decane, terpendole E, dodecane, acetamido-6-anthraquinone and hexadecanol. Also, other compounds such as undecane, dibutyl-disulfide, undecane, octadecenal, paganin, talathermophilin, dactylarin, tolypyridone A, tolypyridone B, pyridoxatin and destruxin were identified, reported in literature to possess antibacterial, antifungal and insecticidal properties. This is the first report of occurrence of both fungi from India and pioneer demonstration of T. cylindrosporum for RKN management.